The Digital Revolution in Healthcare: Advantages of Electronic Health Records Over Paper Files - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The healthcare industry is undergoing a profound transformation, moving away from the cumbersome, error-prone system of paper files toward a more efficient, ...
Keywords: Digital Health; Artificial Intelligence; Patient Care; Machine Learning; Clinical Decision Support